Ethnocentrism and Bias Incidents: Is There a Common Thread? - Rifka Pratama (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2019)
This paper discusses the concepts of culture, ethnocentrism, and bias incidents targeting minority groups, in this case Muslims, in the US. The discussion about the concepts of culture is needed to give a comprehensive understanding of culture and other related topics. It helps to understand the basis of ethnocentrism. Further, it elaborates on both the concept of ethnocentrism and bias incidents that occur in America to find whether there is a common thread between the understanding and the phenomena or not. The study found that ethnocentrism could be the cause of bias incidents targeting minority groups in America. The data is obtained by using the library research method. Keywords: Culture; Ethnocentrism; Bias Incidents; America.